Bits and Pieces: early Bronze Age stone bracers from Ireland - Fiona Roe; Ann Woodward (Internet Archaeology, 2009)
Large numbers of bracers from Ireland were illustrated and published by Peter Harbison in 1976. In association with the preparation of a similar corpus of the bracer material from England (as part of a Birmingham University Leverhulme project on Early Bronze Age grave goods), 32 Irish bracers housed at the National Museum of Ireland, Dublin, have been re-examined. Consideration of lithology showed that far more of the bracers were made from red jasper than was evident from Harbison's publication. Other rocks employed were mainly grey-brown in colour and included a few examples of porcellanite from the Group IX Neolithic axe factory sites. Detailed study of fragmentation and traces of manufacture showed that more than half of the bracers had been broken in antiquity, and then reworked for use as pendants. This article will examine all these aspects, and will compare the results with the different patterns of rock type, colour and fragmentation found in England and Scotland.